Molecular modeling and theory in chemical engineering - Chakraborty, Arup (Advances in chemical engineering, 2001)
In recent years chemical engineers have become increasingly involved in the design and synthesis of new materials and products as well as the development of biological processes and biomaterials. Such applications often demand that product properties be controlled with precision. Molecular modeling.